Lecture recordings to support learning: A contested space between students and teachers. (October 2019) - Morris, Neil P.; Swinnerton, Bronwen; Coop, Taryn
Abstract: Universities, globally, are increasingly offering students a blended learning approach to support their campus-based education, through use of a wide range of educational technologies, tools and systems. Research has demonstrated that blended learning offers at least equivalent learning outcomes for students, and enhances flexibility, inclusivity, engagement and motivation. Many universities across the world (including Australia, the US, Canada, Singapore, Qatar, and across Europe) have adopted lecture capture as a means to support a blended learning approach, and students have strong positive perceptions about the value of lecture recordings to enhance their learning and support their education. However, research shows that teaching staff are generally less positive about the value of lecture capture, believing it to diminish the value of the live lecture experience, reduce learning, and encourage student absenteeism from lectures. In this study, we used mixed methods and repeated cross-sectional data collection to investigate the use and value of lecture recordings from the perspective of students and teaching staff in a large campus-based university, employing a blended learning approach. Our data show that students make significant use of lecture recordings, throughout the academic session, and place great value on recordings for note-taking, more in-depth understanding or clarification, and assessment preparation. As a result, students have high expectations about the availability and quality of recordings. Teaching staff reported a range of reservations about the value of lecture recordings, including its impact on teaching style, and strong concerns about the negative impact of lecture recordings on students learning and attendance. Our data show that over 80% of students attended recorded lectures, but lectures that weren't recorded had significantly higher attendance. In conclusion, our research demonstrates a contested space between staff and students in relation to the use and value of lecture recordings, a contested space that will need to be debated and resolved as universities grow their use of blended learning. This study contributes significantly to this global debate by its use of a wide range of additional data sets to delve further and provide a more nuanced view of this space. Highlights: Students use lecture recordings during term time for learning, and for assessment preparation and examination revision Students request more lecture recordings and quicker access to recordings Students attendance when lectures are recorded is significantly lower Staff have mixed views on the effectiveness of lecture recordings to support learning Staff perceptions of the value of lecture recordings change over time